China's neighbors : who is influencing China and who China is influencing in the new emerging Asia. (China Briefing, The Practical Application of China Business,, 2012)
A look at China's relationship with its 14 neighbor countries: Afghanistan, Bhutan, India, Kazakhstan, Kyrgyzstan, Laos, Myanmar, Mongolia, Nepal, North Korea, Pakistan, Russia, Tajikistan and Vietnam. This book presents a basic economic overview of each respective country and commentary on the country's relationship with China - economic, political and otherwise. An excellent resource for the China-watcher hoping for a broad 360 degree, cross-border understanding of the country. "Whether you are a newcomer to China or already doing business here, you should not be without China Briefing. They are the best in their field and an essential part of any multinational businessman's intelligence on China." -Jack Perkowski, chairman and founder, ASIMCO Technologies; author, "Managing the Dragon" "China Briefing is an established and well respected provider of good quality, useful China legal, tax and business operational information and is a great resource to European investors." -Joerg Wutte, former president, European Chamber of Commerce, Beijing "China Briefing is a must-read resource for anyone involved in China business. With so much material available on the mysteries of doing business in China, it is refreshing to read these practical, down to earth guides. They are well produced, easy to read, and incredibly insightful." -Michael Cronin, COO, Peony Capital, Beijing